Melukis dengan teknik tarikan benang pada pembelajaran Seni Budaya dan Keterampilan (Studi Deskriptif di kelas II SDN 87 Kota Bengkulu) - Verona Elfa; Hasnawati; Dwi Anggraini (Universitas Bengkulu, 2023)
This type of research is qualitative descriptive research, with participant observationtechniques. The purpose of this study is to describe the process of making and painting artwork with yarn pull techniques in class II Culture and Skills SBK study were all class II students of SDN 87 Bengkulu city, totaling 26 people. The research instrument was a human instrument, using observation guidelines, interview guidelines and documentation guidelines. Data collection techniques in the form of observation, interviews and documentation. Data analysis of the process of making the work is done by analyzing the data then reducing, displaying, and drawing conclusions. The results of the study are (1) The process of making painting works with the technique of pulling thread begins with the distribution of tools and materials in the form of newsprint, mattress yarn, dyeing place, HVS paper and coloring. Followed by folding the paper in two. Next dip the yarn into the dye. Then the thread is put on paper and the last is the pulling of the thread. (2) All works of art in painting with the technique of pulling threads made by students contain elements and principles of fine art. Elements of art on the results of painting with yarn pull techniques have all been applied.